ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEMAMPUAN INSTRUKTUR PADA KANTOR BALAI LATIHAN KERJA INDUSTRI DI JAYAPURA - Marlissa, Elsyan Rienette (Lampung University)
Â Balai Latihan Kerja IndustriÂ in Jayapura plays a very important role in building the skills of dropped out students or job seekers in Jayapura. Thus study attempts to investigate the factors affecting the instructorsâability. The result of the study reveals that (1) t test for the variables of education,experience and age show that: t-hitung> t table, this suggests that those variables affect the instructorsâ skill significantly. (2) F test (Fisher Test) F-hitung (164.765> - table (3.68) this means that the dependent variables (the education, the experience, and the age of the instructors simultaneously influence the independent variable that is instructorsâ skill (Y). (3) The Determinant Coefficient (RÂ²) indicates tight relationship between independent variable and dependent variables. The score of RÂ²=0,971 suggests that 97.1% of instructorsâskill can be described by the educational background,experience, and age and the rest 2.9% can be described by other factors such as stratification and wealth of the instructors.